ІГРОВЕ НАВЧАННЯ ЯК ЗАСІБ АКТИВІЗАЦІЇ КОМУНІКАТИВНОЇ ПОЗИЦІЇ УЧНІВ (Педагогіка вищої та середньої школи, 2007)
The prospect of using imitation and playing teaching as a way of stimulation and formation of active communicational position of pupils in the studing process are examined in the article.